Alteration of Sarcoplasmic Reticulum Ca2+ Release in Skeletal Muscle from Calpain 3-Deficient Mice - Govindan Dayanithi; Isabelle Richard; Cédric Viero; Elsa Mazuc; Sylvie Mallie; Jean Valmier; Nathalie Bourg; Muriel Herasse; Isabelle Marty; Gérard Lefranc; Paul Mangeat; Stephen Baghdiguian (International Journal of Cell Biology)
Mutations of Ca2+-activated proteases (calpains) cause muscular dystrophies. Nevertheless, the specific role of calpains in Ca2+ signalling during the onset of dystrophies remains unclear. We investigated Ca2+ handling in skeletal cells from calpain 3-deficient mice. [Ca2+]i responses to caffeine, a ryanodine receptor (RyR) agonist, were decreased in −/− myotubes and absent in −/− myoblasts. The −/− myotubes displayed smaller amplitudes of the Ca2+ transients induced by cyclopiazonic acid in comparison to wild type cells. Inhibition of L-type Ca2+ channels (LCC) suppressed the caffeine-induced [Ca2+]i responses in −/− myotubes. Hence, the absence of calpain 3 modifies the sarcoplasmic reticulum (SR) Ca2+ release, by a decrease of the SR content, an impairment of RyR signalling, and an increase of LCC activity. We propose that calpain 3-dependent proteolysis plays a role in activating support proteins of intracellular Ca2+ signalling at a stage of cellular differentiation which is crucial for skeletal muscle regeneration.